Selenium Supplementation and the Incidence of Preeclampsia in Pregnant Iranian Women: A Randomized, Double-Blind, Placebo-Controlled Pilot Trial - Fatemeh Tara; Gholamali Maamouri; Margaret P. Rayman; Majid Ghayour-Mobarhan; Amirhossein Sahebkar; Omid Yazarlu; Shaida Ouladan; Shima Tavallaie; Mohsen Azimi-Nezhad; Mohammad T. Shakeri; Hasan Boskabadi; Mohammadreza Oladi; et al. (Elsevier, 2010)
Objective: Recent studies have reported that antioxidant status, including serum selenium concentrations, is altered in women who develop preeclampsia. We wished to examine the effects of selenium supplementation in the prevention of preeclampsia in high-risk pregnant women. Design: We carried out a randomized, double-blind, placebo-controlled pilot trial. A total of 166 primigravid pregnant women, who were in the first trimester of pregnancy, were randomized to receive 100 μg of selenium (n = 83; dropouts, n = 22) or a placebo (n = 83; dropouts, n = 19) per day until delivery. The incidence of preeclampsia, serum selenium concentrations, lipid profile and high-sensitivity C-reactive protein status were evaluated at baseline and at the end of the study. Results: Supplementation with selenium was not associated with any reported major side effects and was associated with a significant increase in mean serum selenium concentrations at term (p < 0.001). In contrast, mean serum selenium concentrations remained unchanged in the control group (p = 0.63). The incidence of preeclampsia was lower in the selenium group (n = 0) than in the control group (n = 3), although this was not statistically significant (p > 0.05). After treatment, systolic and diastolic blood pressure, serum total cholesterol, triglycerides, low-density and high-density lipoprotein cholesterol, and high-sensitivity C-reactive protein were significantly increased in both groups compared with pretreatment levels (p < 0.05). Conclusion: Our findings indicate that selenium supplementation in pregnant women may be associated with a lower frequency of preeclampsia.